Advanced digital architectures for model-driven adaptive enterprises - Kulkarni, Vinay, 1966-; Reddy, Sreedhar, 1963-; Clark, Tony (College teacher); Barn, Balbir S. (Advances in e-business research series., 2020)
"This book explores the characteristics of a digital enterprise and examines the technological, socio-economic, and cultural challenges that are caused by the influence of digital forces such as social media, robotics, artificial intelligence etc"--